Cost Comparison Between Stone Mastic Aspahlt (Sma) And Asphalt Concrete Wearing Course (Acw20) - Mohd Arifin Harahap, Rohimah Khoiriyah (2005)
Stone Mastic Asphalt (SMA) technology has been introduced to Malaysian construction industry since the 1990s. Since then, several trial lay projects were carried out to study the performance of the mix. However the acceptability of SMA among local road agency is quite discouraging due to previous reports on the high cost of SMA. However a Malaysian study reported that the construction cost of SMA is actually 10 % to 15% less than the conventional mix. Hence, the study aims to clarify this matter by comparing the construction cost of SMA and ACW20 by using significant cost elements identified by a multiple regression analysis. The analysis covered 27 SMA and ACW20 projects in Selangor. Cost data was collected via a standardized questionnaire. The result indicates that the construction cost of SMA can be comparable to ACW20 if the material cost does not exceed RM 102/ton and the thickness does not exceed 35 mm. Finally, the study revealed that the construction cost of a thinner SMA layer can be made compatible with the conventional mix. Furthermore a thin SMA layer performs much better than thicker asphalt concrete surfacing as indicated by various local and overseas studies.